Freud - Wollheim, Richard (Suffolk Fantana/Collins, 1971)
This intellectual biography of Freud presents a fresh and thorough analysis of the whole body of his writings. Each of these is studied in its context, and their chronology is shown to be of great importance. The author demonstrates how Freud's exploratory and sometimes hesitant efforts to explain all that he discovered of mental abnormality are to be properly understood only in light of his quest for a general theory of the mind. This reissue contains a new Preface by Professor Wollheim that takes account of recent critical work on Freud.